Understanding Electrolytes and Interface Chemistry for Sustainable Nonaqueous Metal–CO2 Batteries - Bijiao He; Yunnian Ge; Fang Zhang; Huajun Tian; Yan Xin; Yong Lei; Yang Yang (Nano-Micro Letters)
Highlights This review focuses on the design principles and basic characteristics of electrolytes, as well as how to construct a stable electrode–electrolyte interface. Perspectives on how electrolytes influence CO2 redox pathways are consolidated and proposed. The electrochemical reaction mechanism and interfacial evolution of nonaqueous metal–CO2 batteries in different electrolyte systems are highlighted. The electrode/electrolyte interface challenges encountered by nonaqueous metal–CO2 batteries are thoroughly discussed, along with corresponding optimization strategies.